Predictors of support for anti-weight discrimination policies among Canadian adults - Levy, Matthew; Forouhar, Vida; Edache, Iyoma Y.; Alberga, Angela S. (Frontiers in Public Health, 2023)
Introduction: Weight discrimination of individuals with overweight or obesity is associated with adverse mental and physical health. Weight discrimination is prevalent in many sectors such as within workplaces, where individuals with overweight and obesity are denied the same opportunities as individuals with lower weight status, regardless of performance or experience. The purpose of this study was to understand the Canadian public’s support or opposition of anti-weight discrimination policies and predictors of support. It was hypothesized that Canadians will show support of anti-weight discrimination policies to some extent. Methods: A secondary analysis was conducted on a previous cross-sectional sample of Canadian adults (N=923, 50.76% women, 74.4% White) who responded to an online survey assessing weight bias and support of twelve anti-weight discrimination policies related to societal policies (e.g. implementing laws preventing weight discrimination) and employment-related policies (e.g. making it illegal to not hire someone due to their weight). Participants completed the Causes of Obesity Questionnaire (COB), the Anti-Fat Attitudes Questionnaire (AFA) and the Modified Weight Bias Internalization Scale (WBIS-M). Multiple logistic regressions were used to determine predictors of policy support. Results: Support for policies ranged from 31.3% to 76.9%, with employment anti-discrimination policies obtaining greater support than societal policies. Identifying as White and a woman, being over the age of 45 and having a higher BMI were associated with an increased likelihood of supporting anti-weight discrimination policies. There were no differences between the level of support associated with attributing obesity to behavioural or non-behavioural causes. Explicit weight bias was associated with a reduced likelihood of supporting 8/12 policies. Weight Bias Internalization was associated with an increased likelihood of supporting all societal policies but none of the employment policies. Conclusions: Support for anti-weight discrimination policies exists among Canadian adults, and explicit weight bias is associated with a lower likelihood of supporting these policies. These results highlight the need for education on the prevalence and perils of weight discrimination which may urge policy makers to consider weight bias as a form of discrimination that must be addressed. More research on potential implementation of anti-weight discrimination policies in Canada is warranted.